A practical quantification method for Heinz bodies in birds applicable to rapid response field scenarios. (6th December 2012) - Fallon, Jesse A.; Hopkins, William A.; Fox, Lee
Abstract Oil‐induced oxidative injury to red blood cells results in Heinz body hemolytic anemia. Here, we evaluated three Heinz body staining techniques in brown pelican (Pelecanus occidentalis) blood. Using a range of in vitro acetylphenylhydrazine incubations, we validated a field‐adapted technique against laboratory wet‐mounts and verified the stability of this technique for one month following preparation. Employing this technique during petrochemical spill responses allows for delays between sample collection and analysis. Environ. Toxicol. Chem. 2013;32:401–405. © 2012 SETAC